2020
DOI: 10.1111/pcmr.12924
|View full text |Cite
|
Sign up to set email alerts
|

Melanin‐concentrating hormone like and somatolactin. A teleost‐specific hypothalamic‐hypophyseal axis system linking physiological and morphological pigmentation

Abstract: Plastic adaptation to match the skin colour to the surrounding is key to survival. Two biological responses in skin colour are associated with background adaptation. A fast “physiological response” that aggregates/disperses the pigment organelles of skin chromatophores, and a slow “morphological response” that alters the type and/or density of pigment cells in the skin. Both responses are linked by unknown mechanisms. In this review, we discuss the role in skin colour regulation of two molecules that form part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In fish models, PRL is involved in a wide range of physiological functions, including reproductive migration [ 33 ], gonadal maturation [ 34 ], reproductive cycling [ 35 , 36 ], nesting and brooding behaviors [ 37 ], and osmoregulation [ 38 ]. As the latest member of the growth hormone (GH)/PRL family, somatolactin was a pituitary hormone unique to fish species and has been reported to play a functional role in the regulation of reproduction [ 39 ], growth [ 40 ] and pigmentation [ 41 ]. These results, as a whole, suggested that HK2 was involved in pituitary regulation of PRL and SLα mRNA expression, which presumably may contribute to the reproduction and growth metabolism in teleost.…”
Section: Discussionmentioning
confidence: 99%
“…In fish models, PRL is involved in a wide range of physiological functions, including reproductive migration [ 33 ], gonadal maturation [ 34 ], reproductive cycling [ 35 , 36 ], nesting and brooding behaviors [ 37 ], and osmoregulation [ 38 ]. As the latest member of the growth hormone (GH)/PRL family, somatolactin was a pituitary hormone unique to fish species and has been reported to play a functional role in the regulation of reproduction [ 39 ], growth [ 40 ] and pigmentation [ 41 ]. These results, as a whole, suggested that HK2 was involved in pituitary regulation of PRL and SLα mRNA expression, which presumably may contribute to the reproduction and growth metabolism in teleost.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that pomc-expressing cells in the RPD adjacent to prl cells express adcyap1r1a, Pacap and Vip may stimulate prl expression through their action on these pomc cells. Sl is a fishspecific member of the Gh/Prl family of pituitary hormones, which has been implicated in skin coloration 44 . Across vertebrates, Prl is a key hormonal regulator of ion and water transport in various tissues, including those responsible for whole-organism ion homeostasis 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Within Cichlasoma dimerus, Sl has been observed to foster melanophore proliferation, whereas in medaka, it selectively orchestrates the morphogenesis of specific pigment cells [145,146]. Further investigations unveil a close physiological and morphological interdependence between Mch and Sl in effecting body color changes, collectively influencing pigment cell differentiation [147]. Additionally, prolactin has been noted in Nile tilapia (Oreochromis niloticus) to disperse erythrophores and xanthophores, thereby facilitating the development of corresponding skin hues [148,149].…”
Section: Hormonal Influencesmentioning
confidence: 99%